2006
DOI: 10.1128/jvi.80.10.4705-4716.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Diversification of Virus-Specific T Cells following Immunization of Human Immunodeficiency Virus Type 1 (HIV-1)-Infected Individuals with a Recombinant Modified Vaccinia Virus Ankara/HIV-1 Gag Vaccine

Abstract: Affordable therapeutic strategies that induce sustained control of human immunodeficiency virus type 1 (HIV-1) replication and are tailored to the developing world are urgently needed. Since CD8 ؉ and CD4 ؉ T cells are crucial to HIV-1 control, stimulation of potent cellular responses by therapeutic vaccination might be exploited to reduce antiretroviral drug exposure. However, therapeutic vaccines tested to date have shown modest immunogenicity. In this study, we performed a comprehensive analysis of the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
67
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 40 publications
4
67
1
Order By: Relevance
“…Thus, in our initial rhesus macaque study using polyepitope immunogen HW and the same pTH and MVA vectors as used here, we showed that the DNA prime-rMVA boost regimen was more potent for induction of T cells than MVA alone [35,36], and that the tetramer frequencies of vaccine-induced T cells peaked 1 wk after the rMVA dosing and decreased thereafter [36]. These results are similar to our recent data in humans [26,27], with the difference in healthy HIV-1-uninfected individuals that in NHP an efficient boost was delivered even with the second and third rMVA dosing [36]. Here, we showed that vaccineinduced responses were detectable over 1 year after vaccination.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, in our initial rhesus macaque study using polyepitope immunogen HW and the same pTH and MVA vectors as used here, we showed that the DNA prime-rMVA boost regimen was more potent for induction of T cells than MVA alone [35,36], and that the tetramer frequencies of vaccine-induced T cells peaked 1 wk after the rMVA dosing and decreased thereafter [36]. These results are similar to our recent data in humans [26,27], with the difference in healthy HIV-1-uninfected individuals that in NHP an efficient boost was delivered even with the second and third rMVA dosing [36]. Here, we showed that vaccineinduced responses were detectable over 1 year after vaccination.…”
Section: Discussionsupporting
confidence: 87%
“…Through gradual pre-clinical and clinical protocol improvements, we were able to demonstrate priming of HIV-1-specific T cell responses in 8/8 healthy and boost pre-existing HIV-1-specific responses in 16/16 HIV-1-infected vaccine recipients [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Study participants were HAART-treated HIV-1-seropositive subjects with CD4 + T cell counts >300 cells/lL and plasma viral RNA <50 copies/mL (Roche Amplicor assay) for at least 12 months. Participants' clinical details and the study bleed schedule have been described [23]. All subjects gave written informed consent and remained on HAART throughout the study.…”
mentioning
confidence: 99%
“…Using dendritic cells infected with poxvirus encoding CEA and co-stimulatory molecules B7-1, ICAM-1 and LFA-3 activates potent CEA-specific immune responses [51]. Recent clinical studies indicated that MVA expressing HIV-1 Gag coupled to other CD8+ T-cell epitopes could induce multifunctional HIV-1-specific T cells in healthy subjects or in individuals with chronic HIV-1 infection [13,52].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of MVA vector-based vaccines have entered into clinical trials [5][6][7][8][9][10][11][12]. Recent studies demonstrated that administration of MVA carrying HIV-1 Gag p24/p17 to HIV-1 infected individuals was safe and feasible [13]. However, no such MVA-based cytomegalovirus (CMV) vaccine has yet to reach the clinic.…”
Section: Introductionmentioning
confidence: 99%